2016
DOI: 10.4149/bll_2016_068
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of argyrophilic nucleolar organizing region

Abstract: BACKGROUND: Ischemia/reperfusion (I/R) injury is a complex event frequently observed in vascular surgery and can cause functional and structural cell damage. Nucleolar-organizing regions (NORs) are sites of the ribosomal genes located on chromosomes and can be stained with silver when they are active. Thus these proteins are named as argyrophilic-NOR (AgNOR)-associated proteins. We aimed to investigate any possible effects of renal I/R injury on the NOR protein synthesis and association between the AgNOR prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…Imamoglu et al [13] reported that the number of AgNOR was significantly increased in children with Down syndrome. Nisari et al [14] reported that the number of AgNOR proteins could be used as an indicator of ischaemia/reperfusion injury. Rao et al [15] found that the number of AgNORs increased significantly in lichen planus and leukoplakia cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imamoglu et al [13] reported that the number of AgNOR was significantly increased in children with Down syndrome. Nisari et al [14] reported that the number of AgNOR proteins could be used as an indicator of ischaemia/reperfusion injury. Rao et al [15] found that the number of AgNORs increased significantly in lichen planus and leukoplakia cases.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] The relationship between AgNOR and various cancer types and some disorders such as leukoplakia, lichen planus, oral submucosal fibrous, prostatic hyperplasia, neuronal damage and Down syndrome was investigated. [12][13][14][15] However, there have been no reports investigating the relationship between AgNOR and atopic dermatitis. The aim of this study was to investigate the relationship between atopic dermatitis and AgNOR in paediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…10 The simplicity and cost-effectiveness of the present AgNOR technique make this a valuable diagnostic method. 14,15 In addition to the detection of the number, size and shape of AgNORs, the measurement of the total AgNOR area and the total nuclear area used for the calculation of the TAA/TNA ratio is also important. 14 Calculation of the TAA/TNA ratio reflects the protein synthesis capacity of the cells, which provides information about the metabolic and proliferative activity of each cell.…”
Section: Introductionmentioning
confidence: 99%
“…14 Calculation of the TAA/TNA ratio reflects the protein synthesis capacity of the cells, which provides information about the metabolic and proliferative activity of each cell. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…Thus, those proteins are referred to as argyrophilic NOR-associated proteins (AgNORs), while the silver-staining method is the most reliable to show nucleoli during the interphase (24). Numerous studies have been carried out on the importance of the interphase quantity of AgNOR proteins in hair root cells of humans (25,26), buccal epithelial and blood cells of Down syndrome infants and healthy persons (27)(28)(29), possible effects of carbonmonoxide (CO) exposure on the AgNOR protein synthesis of the cells of the heart, lung and femoral muscle (30)(31)(32)(33) and ischemia/reperfusion injury (34). However, to our knowledge, there is no study about the relation between AgNOR proteins and the effects of rhamnetin exposure on EST in literature.…”
Section: Introductionmentioning
confidence: 99%